Analisis Pengaruh Rasio Likuiditas dan Rasio Aktivitas Terhadap Rasio Profitabilitas pada Industri Farmasi Tahun 2020-2022 - Nurusyifa Amelia; Chandra Fitriyani C.M; Dorifahtu Afirstantian Maharani; Melinda Magdarina; Cholis Hidayati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The main purpose of writing this article is to analyze the influence of liquidity and activity ratios on profitability in the pharmaceutical industry in 2020-2022. Independent variables used in this study as follows liquidity (X1) is measured using the Current Ratio (CR) and activity (X2) is measured using the Total Asset Turnover (TATO), and the dependent variable is used profitability (Y) is measured using the Return on Assets (ROA). The population of this study is the entire pharmaceutical industry in Indonesia for the period 2020-2022. The samples used were 4 pharmaceutical companies, namely Kalbe, Indofarma, Kimia Farma, and Pyridam Farma. In this study the data analysis used multiple linear regression analysis (t test and F test) which is processed with SPSS 22. Judging from the multiple linear regression model, the results of the T test (partial) states that from liquidity (CR) there is a positive and significant influence on profitability (ROA), and activity (TATO) there is a negative and insignificant influence on profitability (ROA). From the day of the F test showed that liquidity (CR) and activity (TATO) simultaneously had a positive and significant effect on profitability (ROA).